THE RISALAH FI TADBIR SAFAR AL-HAJJ - ROFIQOH, LILIK (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
It is well known that a large amount of knowledge had been transformed by the Greek's scientist through the works of the scribes who translated various knowledge into Arabic who then retranslated them info other languages. One of the important works of the Greek scientist is a treatise on Medical Regime for the Pilgrims to Mecca that was edited by Gerrit Bos. The author of this work, a Christian scholar named Qusta' ibn Luqa, knows the condition of Mecca quite well that he could write such a complete guide on medicine for somebody who wanted to perform the pilgrimage to the holy city. This, this article aims at describing this prominent work of Qusta' ibn Luqo through the text edition written by Gerrit Bos. Keywords: Qusta' ibn Luqo, Gerrit Bos, manuscript, pilgrimage